ALAT PENGHITUNG BENIH IKAN DENGANMEKANISME âIKAN DIAM SENSOR BERGERAKâ MENGGUNAKAN SENSOR OPTIK FOTOTRANSISTOR BERBASIS MIKROKONTROLER - , GANANG NARAYANA SWAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fish hatchery operations is spearheading the successful cultivation of freshwater fish. In the selling process of seed there is still a problem often faced by fish farmers, one of which is the accuracy of the calculation of fish fry. Design of fish fry counting device is aimed to develop a prototype of fish fry counter with stationary fish and moving sensor mechanism high precision. Method of counting was done by moving linearly the sensor automatically using threaded shaft transmitting the motor rotation, detects the presence of fish contained in the receptacle box. The number of counted fish fry was read on the LCD. The result of the designed specifications of the prototype of fish fry counter with stationary fish and moving mechanism with a length of 718 mm, width 413 mm and height 328 mm, 12 V 7.2 Ah batteries, microcontroller Atmel ATmega8, phototransistor sensor, LED light source, DC motor of the sensor move has speed of 21.65 rpm, box reservoir volume (260 x 10 x 30) mm3, the threaded shaft transmitting the motor rotation is 260 mm long, 15 mm diameter and 2 mm pitch. Input fish fry enter the funnel while the output of fish fry go out into the box placeholders that can rotate 180 Âº to the shaft end. The percentage of counting error from individual box placeholders were 7,11 % of box A and 7,71 % of box B. While the percentage error from the combination of box A and box B were 5,1 %, there it was better than of individual box. The calibration resulted a regression equation of y = =1.1818 x - 4.3182 where x = qigab and y = qogab. The slope and intercept of the equation were used for reducing the systematic error persentage by input the both regression parameter into the estimated input counting and that resulted the new regression equation of y = 1 x + 0,00002, where x = qi gab and y from â² gab = (qo gab-b)/m. The calibration results were incorporated into the microcontroller program, a new data collection was gathered to obtain the percentage error of 4.4%. Keywords: counter fish fry, phototransistor sensor, microcontroller, LED, motor, prototype.